Overviewing of weed management practices to reduce weed seed bank and to increase maize yield - Maqsood,Qaiser (2020)
Abstract Background: Weeds are unwanted and undesirable plants which deteriorate the quality of agricultural products and interfere with farming activities. Most of the weeds (indigenous and invasive) seeds get preserved in soil horizons as weed seed bank which ensure their survival leading to the spoilage of quantitative and qualitative functioning of agricultural farms. Objective: To keep weeds below threshold level, elimination of weeds seed before germination can be a viable and pro-ecological approach. To achieve this objective, weed seeds reserved in the soil which serve as an effective pool to ensure their survival necessitate weed-seed bank management. Thus the ultimate goal was to synthesize and analyze research findings on weed seed bank management leading to formulating the most effective strategy encompassing viable control of weeds in maize. Methods: This study reviewed and analyzed the characteristics which impart botanical superiority to weeds and impact of all prevalent weed control strategies on weed seed bank, weeds density and maize yield. The research findings pertaining to different agronomic practices and technological packages were critically analyzed to sort out the most effective and eco-friendly approach to control weed-seed bank and weeds density in maize crop. Results: The synthesis and critical evaluation of research findings pertaining to weed control methods revealed that manual and mechanical methods were eco-friendly but involved expensive labor, while the chemical approach involving the use of herbicides led to serious deterioration of agro-environmental resources. Two or more techniques used in coherence which encompassed deep tillage to burry weeds seed and prevented their germination through mulches of biotic and synthetic materials along with optimizing sowing method especially raised bed technique reduced weed seed bank and weeds density in maize. Conclusions: It is inferred that integrated approach entailing cultural, manual, mechanical and chemical control can be developed as a pro-environmental and farmer friendly approach for weed control by reducing weed seed reserves which can potentially lead to higher economic returns through higher maize yield.